El Greco's Italian paintings (1560-76) based on Bible texts - Estelle Alma Maré (Acta Theologica)
The purpose of this article is to interpret a selection of El Greco’s Italian paintings (1560-1576) based on Bible texts in which ideas current during the Catholic Counter-Reformation are symbolised. At the age of nineteen El Greco, who was born in Crete in 1541 and was initially an icon painter in the Byzantine tradition, went to Venice. Through study and experiment, and by following the examples of other artists who had achieved artistic mastery and was of proven Catholic orthodoxy, he educated himself as an artist in the Western manner. Even during his years as an apprentice El Greco’s art is proof that he aspired to the highest humanly accessible values exemplified by Renaissance artistic theory, humanism and Christian spirituality — all of which later came to fruition in an unprecedented original combination in Toledo, Spain, where he settled permanently in 1577.